Effectiveness Of Patient Counseling On Weight Reduction In Rural And Urban Overweight And Obese Patients - K. SHAILAJA; M. MOHAMMED MOIDEEN; M. ASHOK KUMAR; C. RAMASAMY (International Journal of Pharma and Bio Sciences, 2011)
Obesity and overweight have been reported as a risk factor for diseases such as diabetes, hypertension etc. To make people aware of this fact counseling may play an important role hence; a randomised prospective study was carried out to evaluate the effectiveness of patient counselling in overweight and obese patients on weight reduction in a rural and urban sector of Tamil Nadu, India. A total of 200 subjects were recruited and counseling was provided on diet, physical activity and behavioural modifications. Statistical analysis of data collected revealed that mean levels of body mass index before and after intervention in urban and rural population after three months projected a ‘t’ value of 11.69 and 11.06, respectively which was found to be statistically significant at P=0.001. It was concluded from the study that counseling provided to the patient helped in decreasing total body weight, waist circumference and risk of weight related complications.